EFEKTIVITAS PELAKSANAAN PEMBANGUNAN DESA DI DESA SALIBABU UTARA KECAMATAN SALIBABU UTARA KABUPATEN KEPULAUAN TALAUD - LUMARE, SATRIA; PANGKEY, MASJE; TAMPI, GUSTAAF (Sam Ratulangi University, 2019)
The purpose of this study was to fhid out how effective the implementation villagedevelopment in North Salibabu Village, Salibabu district, Talaud Islands Regency.This study uses a descriptive-qualitative approach. The focus of research on the effectiveness of villagedevelopment is observed in five dimensions of effectiveness, namely production, efficiency, satisfaction/flexibility and development/development, namely the Village Chief, Development research informants,BPD chairman, LPMD Chairpersons, Community members. And community members Datacollection uses interview guidelines, while the analytical technique used is the analysis of interactivemodels from , Miles and Hubernann.The results provide conclusions : (1) The effectiveness ofimplementing village development seen from the dimension of “ production “ has not beenmaximized, but it good enough. (2) The effectiveness of the implementation of village developmentseen from the dimension of ‘’ Efficiency ‘’ has not been maximized, but is has been quite good. (3)The effectiveness of the implementation of the implementation of village development seen from thedimension of ‘’ Satisfaction ‘’ has not been maximized, But it is good enough. (4) The effectivenessof village development seen from the dimension of ‘’ Flexibility Adaptation ‘’ has not beenmaximized, but it is good enough. (5) The effectiveness of village development seen from thedimension of ‘’ Development ‘’ has no been maximized, but Already well enough.Keywords : Effectiveness, Village Development.